NiFe(2)O(4) Nanoparticles Synthesized by Dextrin from Corn-Mediated Sol–Gel Combustion Method and Its Polypropylene Nanocomposites Engineered with Reduced Graphene Oxide for the Reduction of Electromagnetic Pollution - Yadav, Raghvendra Singh (ACS Omega, 2019)
[Image: see text] In this work, nickel ferrite (NiFe(2)O(4)) nanoparticles were synthesized by dextrin from corn-mediated sol–gel combustion method and were annealed at 600, 800, and 1000 °C. The structural and physical characteristics of prepared nanoparticles were studied in detail. The average crystallite size was 20.6, 34.5, and 68.6 nm for NiFe(2)O(4) nanoparticles annealed at 600 °C (NFD@600), 800 °C (NFD@800), and 1000 °C (NFD@1000), respectively. The electromagnetic interference shielding performance of prepared nanocomposites of NiFe(2)O(4) nanoparticles (NFD@600 or NFD@800 or NFD@1000) in polypropylene (PP) matrix engineered with reduced graphene oxide (rGO) have been investigated; the results indicated that the prepared nanocomposites consisted of smaller-sized nickel ferrite nanoparticles exhibited excellent electromagnetic interference (EMI) shielding characteristics. The total EMI shielding effectiveness (SE(T)) for the prepared nanocomposites have been noticed to be 45.56, 36.43, and 35.71 dB for NFD@600-rGO-PP, NFD@800-rGO-PP, and NFD@1000-rGO-PP nanocomposites, respectively, at the thickness of 2 mm in microwave X-band range (8.2–12.4 GHz). The evaluated values of specific EMI shielding effectiveness (SSE) were 38.81, 32.79, and 31.73 dB·cm(3)/g, and the absolute EMI shielding effectiveness (SSE/t) values were 388.1, 327.9, and 317.3 dB·cm(2)/g for NFD@600-rGO-PP, NFD@800-rGO-PP, and NFD@1000-rGO-PP, respectively. The prepared lightweight and flexible sheets can be considered useful nanocomposites against electromagnetic radiation pollution.